Digital entrepreneurship in Africa : how a continent is escaping Silicon Valley's long shadow - Friederici, Nicolas, 1985-; Wahome, Michel; Graham, Mark, 1980- (Cambridge: The MIT press, 2020)
"Digital entrepreneurship has often been viewed as a game changer for African development. Empowered by a single smartphone, the thinking goes, an individual entrepreneur can lay the groundwork for the next Amazon or Apple, and this will jumpstart economic progress on the entire continent. However, the realities of actual African digital entrepreneurship are much more modest. Yes, individual entrepreneurs are able to use digital technology to create new solutions and to enrich their local economic, social, and political communities. However, the results do not typically scale widely, attract venture capital, or grow exponentially. This book provides a much-needed corrective to the hype surrounding digital entrepreneurship in Africa, laying out the empirical facts on the ground of what African digital entrepreneurship actually looks like. The authors worked together on a five-year research project that forms the basis of the book's findings. Their fieldwork was based in 11 cities: Abidjan, Accra, Addis Ababa, Dakar, Johannesburg/Pretoria, Lagos, Kampala, Kigali, Maputo, Nairobi, and Yaoundé. The book aims to understand the opportunities as well as limits that the rise of the internet has brought to ventures in Africa, painting a richer and more realistic picture than what is typically found in the digital innovation literature, media articles, and policy proposals. The authors find that African digital entrepreneurship: is highly unevenly distributed across the continent; is characterized by slow and mostly linear growth; creates digital products largely for customers in urban markets at local and regional scales; depends on entrepreneurial learning and ecosystem evolution, both processes that extend over long periods of time before producing palpable outcomes; consists of strategy innovations like the last-mile platform which blend digital technologies with analog outreach structures; has led to the emergence of new entrepreneurial identities; has triggered cultural and racial tensions as Silicon Valley's ideals have clashed with local realities and reproduced postcolonial dependencies. The authors conclude with a discussion of the implications for entrepreneurs, investors, incubators, local governments, and donors. Rather than focusing on photo ops and buzzwords, stakeholders will have to play a long game, with a goal of focusing on local opportunities for innovating. Copying Silicon Valley is not a recipe for success. Entrepreneurs need to embrace the unique strengths of local contexts, and resources need to be allocated accordingly"--
Hopes and Potentials -- Taking Stock -- Bounded Opportunities -- Viable Strategies -- Uneven Ecosystems -- Transitioning Identities -- Silicon Tensions -- Ways Forward -- Appendix A: Methodology -- Appendix B: Case Study Notes and Market Data.
Includes bibliographical references and index.
Keywords: Electronic commerce -- Africa, Sub-Saharan.; Entrepreneurship -- Information technology -- Africa, Sub-Saharan.; Information technology -- Economic aspects -- Africa, Sub-Saharan.